Womanhood in Africa: An Investigative Appraisal into the Treatment of Women in Two Selected Nigerian Novels - Adewumi, Samuel (International Journal of Language and Literary Studies, 2024)
This paper contributes to a lively discussion in the field of African literature, delving into various misconceptions about women. In a typical African society, there is a perception that women have fewer opportunities compared to their male counterparts who enjoy unrestricted benefits. This research reveals a startling revelation: the roots of these segregations extend far beyond their surface representation. Qualitative findings reveal that women are marginalized at all points of their existence—from the structure of their body, marriage, and childbearing to their total existence as women. Despite feminist scholars analyzing gender from a variety of interdisciplinary perspectives, they have paid little attention to female issues specific to their roles in the home. To fill this gap, this research examines the ways in which female rights, freedoms, and free will are being assessed in the contemporary African societies Adichie and Shoneyin present in their works, Purple Hibiscus and Secret Life of Baba Segi’s Wives, respectively.